Tissue-resident CD169 + macrophages form a crucial front line against plasmodium infection - Gupta, Pravesh (2018)
Tissue macrophages exhibit diverse functions, ranging from the maintenance of tissue homeostasis, including clearance of senescent erythrocytes and cell debris, to modulation of inflammation and immunity. Their contribution to the control of blood-stage malaria remains unclear. Here, we show that in the absence of tissue-resident CD169+ macrophages, Plasmodium berghei ANKA (PbA) infection results in significantly increased parasite sequestration, leading to vascular occlusion and leakage and augmented tissue deposition of the malarial pigment hemozoin. This leads to widespread tissue damage culminating in multiple organ inflammation. Thus, the capacity of CD169+ macrophages to contain the parasite burden and its sequestration into different tissues and to limit infection-induced inflammation is crucial to mitigating Plasmodium infection and pathogenesis.